KAJIAN DESAIN DAN MEKANISME SISTEM PERUMAHAN PUBLIK (DANCHI) DI JEPANG - Yosita, Lucy; Susanti, Indah (Jurnal Arsitektur ARCADE, 2018)
Abstract: Problem of housing in Indonesia is still as a complex problem, with many problems of: land acquisition, backlog 13,8 million of housing need  and high price of house. All of that problems is crucial which need the best and faster solution, therefore analysis and problem solving for this is necessary. In this paper will describe about analysis about public housing in Japan (Danchi) to complete the housing literature study in Indonesia to understand many positive aspects from that. From this analysis can be known that Danchi has many positive aspects, there are : (1). The role of government is as main keyword on Danchi Program by subsidy and totality application, (2). The role of government on  land acquisition is also as the second factor (the justice on right of the land), (3). The simple layout and design is also significant factor to get the price being affordable, (4). The system of payment is based on affordability of community, different salary can be possible to buy/rent housing  (5). The building maintenance is keep on high quality, therefore the age can be longer and the quality can be better.  Keyword: Public Housing, Danchi, Backlog of housing needs Abstrak: Masalah perumahan di Indonesia masih merupakan masalah yang kompleks, dengan aneka masalah yakni: permasalahan tanah, backlog kebutuhan rumah sebanyak 13,8 juta, dan tingginya harga rumah. Semua masalah ini adalah masalah penting yang masih memerlukan solusi yang terbaik dan paling efisien, maka dari itu analisis dan pemecahan masalah adalah sangat penting. Dalam telaah literatur ini akan menganalisis dan membahas mengenai nilai-nilai positif mengenai perumahan di Jepang (Danchi) untuk melengkapi kajian literarur mengenai perumahan dan permukiman di Indonesia. Dari analisis dapat diketahui bahwa : (1). Pranata dan prosedur penanganan pihak pemerintah yang konsisten dan berkeadilan, (2). Penataan lahan, (3). Layout dan desain yang sederhana dan efektif, (4). Sistem pembayaran dan penyewaan sesuai dengan tingkat kemampuan (level of payment) dan (5) Pemeliharaan bangunan secara high quality, adalah prasyarat untuk usia dan kualitas bangunan yang lebih baik.Kata Kunci: Perumahan massal (public housing), Danchi dan Kebutuhan perumahan (housing needs)